Surgical treatment of prostate cancer - Jassem, Jacek; Matuszewska, Katarzyna; Matuszewski, Marcin (Contemporary Oncology/Współczesna Onkologia, 2003)
The importance of prostate cancer is growing with the increasing life expectancy. Along with the popularization of screening programs, increasing awareness of men and wide access to PSA evaluation on one hand, and improvement of diagnostic methods on the other, more cancers are detected in an organ-confined stage, suitable for radical treatment. Radical prostatectomy, besides radiotherapy, is a fundamental method of treatment of such cases. The improvement of surgical techniques has considerably decreased the risk of postoperative complications, and the patient quality of life after treatment seems to be satisfactory. Further improvements are expected with the development of laparoscopic technology. Proper patient selection for the operation remains an important issue. Current diagnostic methods (PSA, digital rectal examination, bone scintigraphy, CT, MRI) do not eliminate a significant proportion of incompletely resected tumors. Thus, a meticulous pathological examination of the biopsy specimen taken before the operation is of particular value. After the operation, the PSA level should drop to undetectable values and this makes PSA a useful and precise marker of treatment monitoring. The outcome of the treatment is still difficult to predict due to slow cancer progression and a large number of co-existing age-related diseases. Nevertheless, radical prostatectomy seems to be a very effective treatment in patients with organ-confined prostate cancer and with life expectancy of more than 10 years.